Talking God in Society: Multidisciplinary (Re)constructions of Ancient (Con)texts. Festschrift for Peter Lampe. Vol. 1: Theories and Applications - Eisen, Ute E.; Mader, Heidrun E.; Ebner, Martin; Lampe, Peter; Schreiber, Stefan; Zangenberg, Jürgen (Vandenhoeck & Ruprecht, 2020)
Intro -- Title Page -- Copyright -- Introduction -- Acknowledgements -- 1. Fundamentals of Historiography and Biblical Scholarship: Epistemological, Hermeneutical and Methodological Meta-Reflections -- Elisabeth Schüssler Fiorenza (Harvard University, USA): Bibelwissenschaft in einer globalisierten Welt -- 1. Soziopolitischer Kontext von bibelwissenschaftlicher Interpretation -- 2. Intersektionalität und Kyriarchatsanalyse -- 3. Kyriarchats- und Befreiungsanalyse: Gal 3:28 -- 4. Die Bibel als Artefakt -- Bibliographie -- Halvor Moxnes (University of Oslo, Norway): Constructing Christian Origins in a Secular Age -- 1. Introduction -- 2. Individual Beginnings -- 3. A Dialogue Between Critical Studies and Faith -- 4. Christian Origins in Secular Universities -- 5. Secular Approaches to Christian Origins -- 6. Conclusion -- Bibliography -- Robert L. Brawley (McCormick Theological Seminary, USA): Navigating History and Collective Memory in New Testament Interpretation -- 1. Attestation and Paucity of Knowledge -- 2. Social Memory -- 3. Why Then History? -- 4. Conclusion -- Bibliography -- Edwin K. Broadhead (Berea College, USA): Narrative and Neurology: A Beginning -- 1. The Path from the Single Neuron to Long-Term Memory -- 2. From Memory to Narrative -- 3. Memory and the Genealogy of Jesus -- 3.1 Matthew 1:1-17 As Semantic Memory -- 3.2 Matthew 1:1-17 As a Catalyst for Episodic Memory -- 3.3 A Proposal: Matthew 1:1-17 As Iconic Memory -- 4. From Thinking about the Genealogy to Thinking from within the Genealogy -- 5. Conclusion -- Bibliography -- Roy A. Harrisville (Luther Seminary, USA): Biblical Interpretation and the Interpretation of Natural Phenomena -- Preface -- 1. The "Text" -- 2. "Objectivity" -- 3. Presuppositions -- 3.1 Hesitation and Admission -- 3.2 Presuppositions That May Be Affirmed -- 3.3 Presuppositions Open to Challenge.
Description based on publisher supplied metadata and other sources
Keywords: Festschrift; Frühchristentum